(untitled) - Douglas, Sleeter (New York, 2002)
Quickbooks is one of the most powerful tools you'll use in managing your business. It is much more than a bookkeeping system. It's a management tool. When set up and used properly, Quickbooks provides you with detailed information that is essential to making good business decisions. Throughout this book, you will find tips from the ex-perts on how to set up and use Quickbooks to properly provide managers with the information needed to make informed business decisions.
Keywords: Quickbooks,Small business,Small business; Accounting,Computer programs,Finance